2022
DOI: 10.7554/elife.74901
|View full text |Cite
|
Sign up to set email alerts
|

Single-molecule analysis of the entire perfringolysin O pore formation pathway

Abstract: The cholesterol-dependent cytolysin perfringolysin O (PFO) is secreted by Clostridium perfringens as a bacterial virulence factor able to form giant ring-shaped pores that perforate and ultimately lyse mammalian cell membranes. To resolve the kinetics of all steps in the assembly pathway, we have used single-molecule fluorescence imaging to follow the dynamics of PFO on dye-loaded liposomes that lead to opening of a pore and release of the encapsulated dye. Formation of a long-lived membrane-bound PFO dimer nu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 64 publications
(103 reference statements)
2
7
1
Order By: Relevance
“…16,55 A two-step process is also consistent with the observations of Böcking and co-workers. 35 In light of these reports it is tempting to assign our fast-process to dimerisation. However in this experiment, to ensure only assembling complexes are selected, our tracking parameters exclude signals from monomeric PFO.…”
Section: B Cmentioning
confidence: 99%
See 1 more Smart Citation
“…16,55 A two-step process is also consistent with the observations of Böcking and co-workers. 35 In light of these reports it is tempting to assign our fast-process to dimerisation. However in this experiment, to ensure only assembling complexes are selected, our tracking parameters exclude signals from monomeric PFO.…”
Section: B Cmentioning
confidence: 99%
“…Overall our data showed that oligomers can continue growing after insertion, as judged by the reduction in diffusivity of the oligomer that is associated with its insertion into the membrane. In a recent preprint, Boecking and co‐workers use a single‐molecule dye release assay to link stoichiometry to pore formation for PFO on surface‐tethered large unilamellar vesicles [35]; their results also suggest assembly independent of membrane permeabilisation. Together, these results support a model where PFO arcs, currently thought to be kinetically trapped, can continue to grow post insertion.…”
Section: Introductionmentioning
confidence: 99%
“…Single‐molecule force spectroscopy can reveal the energetics of transitions 60 . Total internal reflection fluorescence (TIRF) microscopy can resolve the stoichiometry and diffusion of labelled CDC species assembling on the membrane 61,62 . The high sensitivity and temporal resolution enables detection of very short‐lived events, such as monomer binding, and functional readouts can pinpoint specific steps such as opening of the transmembrane pore 61 .…”
Section: Prepore To Porementioning
confidence: 99%
“…Total internal reflection fluorescence (TIRF) microscopy can resolve the stoichiometry and diffusion of labelled CDC species assembling on the membrane 61,62 . The high sensitivity and temporal resolution enables detection of very short‐lived events, such as monomer binding, and functional readouts can pinpoint specific steps such as opening of the transmembrane pore 61 . These experimental methods are particularly powerful when combined with simulations of processes that are too fast to be resolved with existing imaging technologies, that is, the restructuring of the lipid bilayer that leads to initial opening of the transmembrane pore 63 .…”
Section: Prepore To Porementioning
confidence: 99%
See 1 more Smart Citation